Efficacy and safety of antidepressant augmentation of continued antipsychotic treatment in patients with schizophrenia. (12th February 2018) - Galling, B.; Vernon, J. A.; Pagsberg, A. K.; Wadhwa, A.; Grudnikoff, E.; Seidman, A. J.; Tsoy‐Podosenin, M.; Poyurovsky, M.; Kane, J. M.; Correll, C. U.
Abstract : Objective: To evaluate the efficacy and safety of antidepressant augmentation of antipsychotics in schizophrenia. Methods: Systematic literature search (PubMed/MEDLINE/PsycINFO/Cochrane Library) from database inception until 10/10/2017 for randomized, double‐blind, efficacy‐focused trials comparing adjunctive antidepressants vs. placebo in schizophrenia. Results: In a random‐effects meta‐analysis (studies = 42, n  = 1934, duration = 10.1 ± 8.1 weeks), antidepressant augmentation outperformed placebo regarding total symptom reduction [standardized mean difference (SMD) = −0.37, 95% confidence interval (CI) = −0.57 to −0.17, P  < 0.001], driven by negative (SMD = −0.25, 95% CI = −0.44–0.06, P  = 0.010), but not positive ( P  = 0.190) or general ( P  = 0.089) symptom reduction. Superiority regarding negative symptoms was confirmed in studies augmenting first‐generation antipsychotics (FGAs) (SMD = −0.42, 95% CI = −0.77, −0.07, P  = 0.019), but not second‐generation antipsychotics ( P  = 0.144). Uniquely, superiority in total symptom reduction by NaSSAs (SMD = −0.71, 95% CI = −1.21, −0.20, P  = 0.006) was not driven by negative ( P  = 0.438), but by positive symptom reduction (SMD = −0.43, 95% CI = −0.77, −0.09, P  = 0.012). Antidepressants did not improve depressive symptoms more than placebo ( P  = 0.185). Except for more dry mouth [risk ratio (RR) = 1.57, 95% CI = 1.04–2.36, P  = 0.03], antidepressant augmentation was not associated with more adverse events or all‐cause/specific‐cause discontinuation. Conclusions: For schizophrenia patients on stable antipsychotic treatment, adjunctive antidepressants are effective for total and particularly negative symptom reduction. However, effects are small‐to‐medium, differ across antidepressants, and negative symptom improvement seems restricted to the augmentation of FGAs.